Isolation and characterization of an acrylamide-degrading Antarctic bacterium - Abd. Shukor, Mohd Yunus; Gusmanizar, Neni; Ramli, Johari; Shamaan, Nor Aripin; MacCormack, W. P.; Syed, Mohd Arif (Triveni Enterprises, Lucknow, 2009)
The presence of acrylamide in the environment poses a threat due to its well known neurotoxic, carcinogenic and teratogenic properties. Human activities in various geographical areas are the main anthropogenic source of acrylamide pollution. In this work, an acrylamide-degrading bacterium was isolated from Antarctic soil. The physiological characteristics and optimum growth conditions of the acrylamide-degrading bacteria were investigated. The isolate was tentatively identified as Pseudomonas sp. strain DRYJ7 based on carbon utilization profiles using Biolog GN plates and partial 16S rDNA molecular phylogeny. The results showed that the best carbon sources for growth was glucose and sucrose with no significant difference in terms of cellular growth between the two carbon sources (p>0.05). This was followed by fructose and maltose with fructose giving significantly higher cellular growth compared to maltose (p<0.05). Lactose and citric acid did not support growth. The optimum acrylamide concentration as a nitrogen source for cellular growth was at 500 mgl-1. At this concentration, bacterial growth showed a 2-day lag phase before degradation took place concomitant with an increase in cellular growth. The isolate exhibited optimum growth in between pH 7.5 and 8.5. The effect of incubation temperature on the growth of this isolate showed an optimum growth at 15°C. The characteristics of this isolate suggest that it would be useful in the bioremediation of acrylamide